High stakes assessment policy implementation in the time of COVID-19: the case of calculated grades in Ireland. Issue 2 (3rd April 2021) - Doyle, Audrey; Lysaght, Zita; O'Leary, Michael
Abstract : This paper provides a perspective on the manner in which Irish post-primary teachers interpreted and implemented a set of guidelines created by the Department of Education and Skills (DES) in Ireland when faced with the cancellation of the traditional high stakes Leaving Certificate (LC) examination due to COVID-19. Subject teachers were asked to engage with a system of calculated grades whereby they would estimate a percentage mark and a class rank for each of their students before meeting with school colleagues to agree a final set of data to be submitted for national standardisation. This was a remarkable event in Irish education as teachers had never before been directly involved in assessing their own students for certification purposes. Data from a survey conducted with teachers ( n  = 713) show that a wide variety of evidence was used to support their judgements and that the DES guidelines were not always implemented as intended. Challenges highlighted in the paper include decision making around grade boundaries, the lack of evidence for newer subjects, negotiating with school colleagues, and anticipating the impact of national standardisation. The study findings will be of interest to future initiatives involving the professional judgement of teachers in high stakes contexts.